2012
DOI: 10.1016/j.ygyno.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined expression of KLK4, KLK5, KLK6, and KLK7 by ovarian cancer cells leads to decreased adhesion and paclitaxel-induced chemoresistance

Abstract: This study demonstrates that combined KLK4-7 expression by ovarian cancer cells promotes reduced integrin expression with consequently less cell-matrix attachment, and insensitivity to paclitaxel mediated by complex integrin and MAPK independent interactions, indicative of a malignant phenotype and disease progression suggesting a role for these KLKs in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(75 citation statements)
references
References 58 publications
3
72
0
Order By: Relevance
“…This fact, together with the role of KLK6 in cleavage of ECM proteins, elucidate the contribution of KLK6 to tumor invasiveness and metastasis (Ghosh et al, 2004; Prezas et al, 2006; Seiz et al, 2012). Moreover, KLK6 in concert with KLKs 4, 5, and 7 provokes transforming growth factor (TGF-β) signaling which may be the cause for taxane drug resistance in ovarian cancer (Loessner et al, 2012). Thus, KLK6 expression may be linked to chemoresistence and this may be the reason for the shortened overall survival of the patients, which all had received adjuvant chemotherapy following surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact, together with the role of KLK6 in cleavage of ECM proteins, elucidate the contribution of KLK6 to tumor invasiveness and metastasis (Ghosh et al, 2004; Prezas et al, 2006; Seiz et al, 2012). Moreover, KLK6 in concert with KLKs 4, 5, and 7 provokes transforming growth factor (TGF-β) signaling which may be the cause for taxane drug resistance in ovarian cancer (Loessner et al, 2012). Thus, KLK6 expression may be linked to chemoresistence and this may be the reason for the shortened overall survival of the patients, which all had received adjuvant chemotherapy following surgery.…”
Section: Discussionmentioning
confidence: 99%
“…KLK6 expression is dysregulated in different cancers such as pancreatic (Ruckert et al, 2008), breast (Wang et al, 2008), colon (Vakrakou et al, 2014), and gastric cancer (Kolin et al, 2014). In ovarian cancer, KLK6 overexpression has been reported to be associated with poor prognosis, advanced clinical disease, shorter disease-free and overall survival, and chemotherapy resistance (Diamandis et al, 2003; Kountourakis et al, 2008; White et al, 2009; Loessner et al, 2012; Seiz et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that multi-cellular aggregates, harboring a 3D architecture, are more resistant compared to flat cell cultures [48], and compact aggregates are less responsive to different therapeutic regimes, such as chemotherapies, than scattered aggregates [49]. We have also reported that combined expression of KLK4, KLK5, KLK6, and KLK7 in ovarian cancer cells (OV-KLK) mediates resistance to paclitaxel at higher doses (10, 100 nM) compared to control cells (OV-Vector) when grown as flat cell cultures [28]. When the same cells were grown as aggregates in this study, we observed a similar cell survival effect upon KLK expression and paclitaxel treatment.…”
Section: Resultsmentioning
confidence: 99%
“…When the same cells were grown as aggregates in this study, we observed a similar cell survival effect upon KLK expression and paclitaxel treatment. Interestingly, the expression of β1 integrin was decreased upon KLK expression [28], but upon paclitaxel treatment increased in both KLK-expressing and KLK-deficient aggregates, suggesting a critical function of this integrin in paclitaxel-related resistance, only partially induced by these four KLKs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation